2002
DOI: 10.1180/0026461026660067
|View full text |Cite
|
Sign up to set email alerts
|

Graftonite in phosphatic iron formations associated with the mid-Proterozoic Gamsberg Zn-Pb deposit, Namaqua Province, South Africa

Abstract: Granular aggregates of fine-grained graftonite (Fe,Mn,Ca)3(PO4)2and intergrown wolfeite (Fe,Mn)2(PO4)(OH) occur in amphibolite-facies metamorphosed iron formations associated with the Gamsberg Zn-Pb deposit, South Africa. To date, these minerals were believed to have limited parageneses, being essentially restricted to granitic pegmatites and iron meteorites. This paper is the first report of the occurrence of graftonite and wolfeite in a regionally metamorphosed, iron formation-hosted setting. The aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…OH-end-members are not defined to date (Pasero et al 2010), but Dunn et al (1985) described OH-bearing hedyphane, while OH-dominated phosphohedyphane is indicated by data from Stalder and Rozendaal (2002). In the present contribution, we report analyses supporting the existence of an OH-end-member of mimetite.…”
supporting
confidence: 74%
“…OH-end-members are not defined to date (Pasero et al 2010), but Dunn et al (1985) described OH-bearing hedyphane, while OH-dominated phosphohedyphane is indicated by data from Stalder and Rozendaal (2002). In the present contribution, we report analyses supporting the existence of an OH-end-member of mimetite.…”
supporting
confidence: 74%
“…The prevalence of pyromorphite as opposed to its F-and OH-analogs may be related to the presence of lead as the dominant cation at both the M1 and M2 sites of the apatite structure, which results in larger unit-cell dimensions and makes Cl -, whose ionic radius is markedly greater than those of F -and OH -, the best candidate to occupy the X site. Similarly, F-and OH-analogs of phosphohedyphane have not been previously reported, although Stalder and Rozendaal (2002) report a "calcian pyromorphite" that is very low in Cl and F, which may correspond to the OH-analog of phosphohedyphane. Herein, we report the first occurrence of the F-analog of phosphohedyphane from the Blue Bell claims, near Baker, San Bernardino County, California.…”
Section: Introductionmentioning
confidence: 75%
“…Wolfeite, (Fe,Mn) 2+ 2 (PO 4 )(OH), is a rare phosphate mineral which has been reported in granitic pegmatites (Smeds et al, 1998;Roda et al, 2004) and in metamorphosed phosphatic ironstones (Robinson et al, 1992;Stalder & Rozendaal, 2002). Wolfeite belongs to the triplite-triploidite group of minerals (Strunz & Nickel, 2001;Chopin et al, 2003), which also includes the following phosphates: triplite [(Mn,Fe) 2+ 2 (PO 4 )F; Waldrop, 1969], zwieselite [(Fe,Mn) 2+ 2 (PO 4 )F; Yakubovich et al, 1978], triploidite [(Mn,Fe) 2+ 2 (PO 4 )(OH); Waldrop, 1970], wagnerite [(Mg,Fe 2+ ) 2 (PO 4 )F; Coda et al, 1967], staně kite [(Mn,Fe 2+ ,Mg)Fe 3+ (PO 4 )O; Keller et al, 2006] and joosteite [Mn 2+ (Mn 3+ ,Fe 3+ )(PO 4 )O; Keller et al, 2007].…”
Section: Commentmentioning
confidence: 99%